Broadband-gap perovskite battery, landform regulation and control method thereof and multi-junction laminated battery
By coating specific polymers and N,N-dimethylformamide on the first carrier layer of a wide bandgap perovskite solar cell and heating treatment, the high-dimensional landform of the perovskite film is optimized, and the filling factor regulation problem in the prior art is solved, which significantly improves the efficiency of the solar cell.
Patent Information
- Application Number
- CN202510064107.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to effectively regulate the filling factor of wide-bandgap perovskite solar cells, resulting in a large gap in the theoretical upper limit of its efficiency distance.
The high-dimensional landform of the perovskite film is optimized by sequentially coating the surface of the first carrier layer with poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-din-octylfluorenyl-2,7-diyl)-bromo and N,N-dimethylformamide as the geomorphic modification layer, and heating at 50-200°C for 1-30 min.
This method helps balance carrier transmission, provides additional photocurrent compensation, and improves the filling factor and efficiency of solar cells.
Smart Images

Figure CN119855454A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite cells, and in particular to a wide bandgap perovskite cell and a topography control method thereof, and a multi-junction stacked cell. Background Art
[0002] In recent years, wide bandgap perovskite (bandgap ≥ 1.65eV) solar cells have attracted widespread attention. Compared with conventional bandgap perovskites, wide bandgap perovskite cells have the advantages of good weak light response and easy light transmittance adjustment, so they can be used in a variety of scenarios such as multi-junction stacked cells (such as perovskite-crystalline silicon, perovskite-copper indium gallium selenide, etc.), building integrated photovoltaics (BIPV), indoor photovoltaics, consumer electronics, etc., greatly expanding the potential photovoltaic market.
[0003] However, the efficiency of wide-bandgap perovskites is still far from its theoretical upper limit, which restricts the improvement of its product performance. The efficiency of solar cells is determined by three main parameters: voltage, current, and fill factor. However, the main means currently available in the industry are mostly aimed at improving the voltage and current of wide-bandgap perovskite cells, and there is a lack of effective strategies and methods for regulating the fill factor. In addition, the current control strategies for perovskite films are mostly based on their two-dimensional planar morphology, while means of controlling higher-dimensional morphologies are still missing.
[0004] In view of this, the present invention proposes a topography control method for wide-bandgap perovskite, which achieves the improvement of the fill factor and efficiency of the prepared solar cells through high-dimensional topography optimization, thereby filling the gap in related research methods in the field. Summary of the invention
[0005] The purpose of the present invention is to provide a wide bandgap perovskite cell and a topography control method thereof and a multi-junction stacked cell.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a method for controlling the topography of a wide bandgap perovskite battery, comprising: before preparing a wide bandgap perovskite layer on the surface of a first carrier layer, first coating the surface of the first carrier layer with a layer of poly[(9,9-bis(3"-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromine as a first topography modification layer, heating at 50-100°C for 1-30min, then coating with a layer of N,N-dimethylformamide as a second topography modification layer, and then heating at 50-200°C for 1-30min.
[0008] In an optional embodiment, the concentration of the poly [(9,9-bis(3"-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide is 0.1-10 mg / mL.
[0009] In an optional embodiment, the solvent of the poly[(9,9-bis(3"-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide is an alcohol reagent;
[0010] Preferably, the alcohol reagent includes at least one of ethanol, isopropanol and methanol.
[0011] In an optional embodiment, the coating ratio of the poly [(9,9-bis(3"-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and the N,N-dimethylformamide is 1-100:1-100.
[0012] In an optional embodiment, the poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and the N,N-dimethylformamide are both spin-coated at a spin-coating speed of 4000-6000 for 20-40 seconds.
[0013] In an optional embodiment, the first carrier layer is obtained by coating poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] on a conductive glass substrate;
[0014] Preferably, the conductive glass substrate comprises ITO or FTO;
[0015] Preferably, the concentration of the poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] is 0.1-10 mg / mL;
[0016] Preferably, the thickness of the first carrier layer is 0.5-50 nm.
[0017] In an optional embodiment, the composition of the wide bandgap perovskite layer is ABX3; wherein A is a monovalent cation, B is a metal divalent cation, and X is a halogen element;
[0018] Preferably, A is at least one of formamidine, methylamine, Cs and Rb;
[0019] Preferably, B is at least one of Pb and Sn;
[0020] Preferably, X is at least two of I, Br and Cl.
[0021] In an optional embodiment, after the wide bandgap perovskite layer is prepared, the process further includes sequentially preparing a second carrier layer and a metal electrode on the surface of the wide bandgap perovskite layer.
[0022] In a second aspect, the present invention provides a wide bandgap perovskite cell, which is prepared by the topography control method of the wide bandgap perovskite cell as described in any of the aforementioned embodiments.
[0023] In a third aspect, the present invention provides a multi-junction stacked cell, which includes the wide bandgap perovskite cell as described in the above embodiment.
[0024] The present invention has the following beneficial effects:
[0025] The method for topography control of a wide bandgap perovskite cell provided by the present invention comprises the following steps: sequentially coating the surface of a first carrier layer with poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and N,N-dimethylformamide as a second topography modification layer, and heating at 50-200° C. for 1-30 min. The above treatment is beneficial to the balanced transmission of carriers in the perovskite film, and can provide additional photocurrent compensation. Poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide can modify the interface, improve wettability, and control the crystallinity of the perovskite film, thereby improving the performance of the organic photoelectric device. DMF has high solvation ability and slow crystallization kinetics, which can promote the nucleation and growth of perovskite crystals. The combination of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and N,N-dimethylformamide can slow down the excessively undulating growth of perovskite crystals, thereby forming a hilly landform with moderate undulations, which is more conducive to the balanced transmission of carriers in perovskite films and can provide additional photocurrent compensation. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0027] Figure 1A process flow chart of a wide bandgap perovskite solar cell provided in Example 1 and Comparative Examples 1-2 of the present invention;
[0028] Figure 2 Atomic force microscope three-dimensional test result diagram (a) and scanning electron microscope cross-sectional morphology diagram (b) of the wide bandgap perovskite solar cell provided in Example 1 of the present invention;
[0029] Figure 3 Atomic force microscope three-dimensional test result diagram (a) and scanning electron microscope cross-sectional morphology diagram (b) of the wide bandgap perovskite solar cell provided in Comparative Example 1 of the present invention;
[0030] Figure 4 Atomic force microscope three-dimensional test result diagram (a) and scanning electron microscope cross-sectional morphology diagram (b) of the wide bandgap perovskite solar cell provided in Comparative Example 2 of the present invention;
[0031] Figure 5 This is a voltage-current test curve diagram of the wide bandgap perovskite solar cell provided in Example 1 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0033] The invention provides a method for controlling the topography of a wide bandgap perovskite battery, which comprises: before preparing a wide bandgap perovskite layer on the surface of a first carrier layer, firstly coating the surface of the first carrier layer with a layer of poly[(9,9-bis(3"-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromine as a first topography modification layer, heating at 50-100°C for 1-30min, then coating with a layer of N,N-dimethylformamide as a second topography modification layer, and then heating at 50-200°C for 1-30min.
[0034] In the present invention, by sequentially coating the surface of the first carrier layer with poly[(9,9-bis(3"-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide (PFNBr) and N,N-dimethylformamide (DMF), a perovskite with a "hilly" topography can be obtained. The change in topography can significantly affect the performance of the obtained perovskite cell, such as the photoelectric efficiency and the filling factor. Among them, the hilly topography is more conducive to the balanced transmission of carriers in the perovskite film due to its moderate film undulation, and can provide additional photocurrent compensation.
[0035] Among them, the molecular schematic diagram of PFNBr is PFNBr is a polymer electrolyte that can be dissolved in alcohol solvents such as ethanol, isopropanol, methanol, etc. By dissolving PFNBr in the above solvents to prepare a solution of a specific concentration (0.1-10 mg / mL), it is convenient for subsequent coating. It can effectively avoid the interfacial solubility problem in solution-processed multilayer devices, and it can modify the interface, improve wettability, and regulate the crystallinity of perovskite films, thereby improving the performance of organic optoelectronic devices.
[0036] In the present invention, a layer of DMF is coated on the surface of PFNBr. DMF is a commonly used non-polar solvent, which can make the PFNBr on the surface evenly dispersed to form a uniform film. Compared with other solvents, DMF can improve the stability of perovskite, reduce surface defects, and improve the efficiency of solar cells. DMF has a high solvation ability and slow crystallization kinetics, thereby promoting the nucleation and growth of perovskite crystals.
[0037] In the present invention, the coating ratio of poly[(9,9-bis(3"-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and N,N-dimethylformamide is 1-100:1-100. In the present invention, the two are combined, wherein the Br group contained in the PFNBr molecule can better bind the lead atoms in the perovskite, optimize the crystallization process, and thus improve the interface strength; in addition, the long carbon chain contained therein makes the growth of the perovskite film uneven, thereby reflecting the mountain-type landform. After coating DMF on it, the configuration of the bottom PFNBr molecule can be improved, the long carbon chain group can be relaxed, the orientation consistency can be improved, and then the landform of the perovskite film prepared subsequently can be affected.
[0038] Poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and N,N-dimethylformamide were spin coated at a spin coating speed of 4000-6000 for 20-40 seconds.
[0039] The first carrier layer is obtained by coating poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] with a concentration of 0.1-10 mg / mL on a conductive glass substrate (ITO or FTO); preferably, the thickness of the first carrier layer is 0.5-50 nm.
[0040] The composition of the wide bandgap perovskite layer is ABX3; wherein A is a monovalent cation, B is a metal divalent cation, and X is a halogen element; preferably, A is at least one of formamidine, methylamine, Cs and Rb; B is at least one of Pb and Sn; and X is at least two of I, Br and Cl.
[0041] After the wide bandgap perovskite layer is prepared, a second carrier layer and a metal electrode are sequentially prepared on the surface of the wide bandgap perovskite layer. The preparation of the second carrier layer and the metal electrode can be carried out according to conventional operations, which will not be elaborated in detail in the present invention.
[0042] The wide bandgap perovskite cell prepared by the above-mentioned wide bandgap perovskite cell topography control method has good filling factor and efficiency, and thus has good performance. It can be widely used in the preparation of multi-junction stacked cells.
[0043] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0044] Example 1
[0045] See also Figure 1 This embodiment provides a method for controlling the topography of a wide bandgap perovskite battery, which comprises the following steps:
[0046] (1) Clean the conductive glass substrate (ITO) using deionized water, glass cleaning agent, and alcohol in sequence to clean the substrate.
[0047] (2) A hole transport layer was prepared by coating poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine) (PTAA) on a conductive glass substrate using a solution method. The spin coating speed was 5000 rpm and the spin coating time was 30 s.
[0048] (3) A layer of poly [(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide with a concentration of 5 mg / mL was coated on the surface of the hole transport layer, with a coating amount of 75 μL, a spin coating speed of 5000 rpm, and a time of 30 s, as the first topography modification layer, followed by heating at 100°C for 5 min; a layer of N,N-dimethylformamide was then coated with a coating amount of 90 μL, a spin coating speed of 5000 rpm, and a time of 30 s as the second topography modification layer, followed by heating at 100°C for 10 min.
[0049] (4) Preparation of FA with a concentration of 1.5 M 0.8 MA 0.1 Cs 0.1 PbI 1.8 Br 1.2 A perovskite precursor solution is prepared, wherein the precursor solution solvent is a DMF:DMSO mixed solvent with a volume ratio of 4:1. The prepared 1.5 M perovskite precursor solution is spin-coated on the second topography modification layer by variable speeds: spin coating at a speed of 1000 rpm for 10 s, spin coating at a speed of 5000 rpm for 35 s, and then annealing at 100°C for 20 min to obtain a wide bandgap perovskite layer.
[0050] (5) Preparation of electron transport layer. The electron layer uses PCBM solution (concentration 10 mg / mL), the amount is 55 μL, the spin coating speed is 1000 rpm / s, and the time is 30 s; then use BCP solution (concentration 1 mg / mL), the amount is 60 μL, the spin coating speed is 5000 rpm / s, and the time is 30 s.
[0051] (6) Prepare metal electrodes to complete the preparation of solar cells. The metal electrodes are made of copper, silver, or aluminum and are prepared by physical vapor deposition. The thickness of the electrodes is 100 nm.
[0052] Example 2
[0053] This embodiment is basically the same as embodiment 1, except that the parameters of step (3) are different. In this embodiment, step (3) includes: coating a layer of poly [(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide with a concentration of 10 mg / mL on the surface of the hole transport layer, with a coating amount of 20 μL, as a first topography modification layer; and then coating a layer of N,N-dimethylformamide with a coating amount of 80 μL, as a second topography modification layer, and then heating at 200°C for 5 min.
[0054] Example 3
[0055] This embodiment is basically the same as embodiment 1, except that the parameters of step (3) are different. In this embodiment, step (3) includes: coating a layer of 1 mg / mL poly [(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide on the surface of the hole transport layer in an amount of 100 μL as a first topography modification layer; and then coating a layer of N,N-dimethylformamide in an amount of 30 μL as a second topography modification layer, followed by heating at 60°C for 30 min.
[0056] Comparative Example 1
[0057] See also Figure 1 This comparative example is basically the same as Example 1, except that step (3) in Example 1 is omitted in this comparative example, and subsequent steps (4)-(6) are directly performed on the hole transport layer.
[0058] Comparative Example 2
[0059] See also Figure 1 This comparative example is basically the same as Example 1, except that in step (3) of this comparative example, only a layer of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide is coated on the surface of the hole transport layer as the first topography modification layer, followed by heating at 100°C for 5 minutes. In this comparative example, N,N-dimethylformamide is not coated as the second topography modification layer.
[0060] Comparative Example 3
[0061] This comparative example is basically the same as Example 1, except that in step (3) of this comparative example, only a layer of N,N-dimethylformamide is coated on the surface of the hole transport layer, followed by heating at 100° C. for 10 min. In this comparative example, poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide is not coated.
[0062] Comparative Example 4
[0063] This comparative example is basically the same as Example 1, except that step (3) in this comparative example is: coating a layer of a mixed solution of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and N,N-dimethylformamide on the surface of the hole transport layer, and then heating at 100° C. for 15 min.
[0064] Comparative Example 5
[0065] This comparative example is basically the same as Example 1, except that the heating parameters of step (3) in this comparative example are different. In this comparative example, the heating temperature of PFNBr is 40° C. for 5 min.
[0066] Comparative Example 6
[0067] This comparative example is basically the same as Example 1, except that the heating parameters of step (3) in this comparative example are different. In this comparative example, the heating temperature of PFNBr is 150° C. for 5 min.
[0068] Experimental example
[0069] The solar cells prepared in the above embodiments and comparative examples were tested for photoelectric conversion efficiency. The testing method included: testing the perovskite solar cell under a standard solar spectrum (AM 1.5G), using a Keithley source meter to collect the current and voltage values of the test, obtaining data such as open circuit voltage, short circuit current, and fill factor, and finally calculating the photoelectric efficiency.
[0070] Voc(V) FF <![CDATA[Jsc(mA / cm 2 )]]> PCE(%) Example 1 1.23 0.80 17.68 17.3 Example 2 1.16 0.79 14.69 13.5 Example 3 1.17 0.77 16.62 15.1 Comparative Example 1 1.18 0.72 17.04 14.6 Comparative Example 2 1.19 0.65 17.87 13.9 Comparative Example 3 1.10 0.78 16.9 14.5 Comparative Example 4 1.22 0.78 17.04 16.3 Comparative Example 5 1.19 0.70 14.74 12.36 Comparative Example 6 1.23 0.56 8.86 6.05
[0071] from Figure 2 , Figure 3 , Figure 4 and Figure 5 It can be seen that after the introduction of PFNBr in Comparative Example 2, the perovskite topography fluctuates greatly, and the overall shape is mountainous, which may be related to the change in the perovskite crystallization dynamics process; after additional DMF treatment on PFNBr, the fluctuation of the perovskite is significantly reduced, and the topography becomes hilly, which may be related to the improvement of the orientation and arrangement of PFNBr molecules by DMF treatment (such as Example 1); the perovskite film without any treatment has a conventional planar topography (such as Comparative Example 1).
[0072] As can be seen from the table above, the performance of the battery in Example 1 is the best, and changes in PFNBr concentration and heating annealing temperature and time will have a significant impact on the prepared perovskite battery device. In addition, the efficiency of the battery treated with PFNBr or DMF alone, and the battery treated with a mixture of PFNBr and DMF are weaker than the treatment method of first PFNBr and then DMF, which further illustrates the uniqueness of this process.
[0073] In summary, the method for topography control of wide bandgap perovskite cells provided by the present invention is to sequentially coat the surface of the first carrier layer with poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and N,N-dimethylformamide as the second topography modification layer, and heat at 50-200°C for 1-30min. The above treatment is beneficial to the balanced transmission of carriers in the perovskite film and can provide additional photocurrent compensation. Poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide can modify the interface, improve wettability, and control the crystallinity of the perovskite film, thereby improving the performance of the organic optoelectronic device. DMF has high solvation ability and slow crystallization kinetics, which can promote the nucleation and growth of perovskite crystals. The combination of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and N,N-dimethylformamide can slow down the excessively undulating growth of perovskite crystals, thereby forming a hilly landform with moderate undulations, which is more conducive to the balanced transmission of carriers in perovskite films and can provide additional photocurrent compensation.
[0074] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for controlling landforms of wide bandgap perovskite cells, characterized in that: The method comprises: before preparing a wide bandgap perovskite layer on the surface of a first carrier layer, firstly coating the surface of the first carrier layer with a layer of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromine as a first topography modification layer, heating the layer at 50-100°C for 1-30min, then coating the layer of N,N-dimethylformamide as a second topography modification layer, and then heating the layer at 50-200°C for 1-30min.
2. The method for controlling the topography of a wide bandgap perovskite battery according to claim 1, characterized in that: The concentration of the poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide is 0.1-10 mg / mL.
3. The landform control method of wide bandgap perovskite battery according to claim 1, characterized in that: The solvent of the poly[(9,9-di(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide is an alcohol reagent; Preferably, the alcohol reagent includes at least one of ethanol, isopropanol and methanol.
4. The landform control method of wide bandgap perovskite battery according to claim 1, characterized in that: The coating ratio of the poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and the N,N-dimethylformamide is 1-100:1-100.
5. The method for controlling landform of wide bandgap perovskite battery according to claim 1, characterized in that: The poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide and the N,N-dimethylformamide are both spin-coated at a spin-coating speed of 4000-6000 for 20-40 seconds.
6. The method for controlling landform of wide bandgap perovskite battery according to claim 1, characterized in that: The first carrier layer is obtained by coating poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] on a conductive glass substrate; Preferably, the conductive glass substrate comprises ITO or FTO; Preferably, the concentration of the poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] is 0.1-10 mg / mL; Preferably, the thickness of the first carrier layer is 0.5-50 nm.
7. The landform control method of wide bandgap perovskite battery according to claim 1, characterized in that: The wide bandgap perovskite layer has a composition of ABX3, wherein A is a monovalent cation, B is a metal divalent cation, and X is a halogen element; Preferably, A is at least one of formamidine, methylamine, Cs and Rb; Preferably, B is at least one of Pb and Sn; Preferably, X is at least two of I, Br and Cl.
8. The method for controlling landform of wide bandgap perovskite battery according to claim 1, characterized in that: After the wide bandgap perovskite layer is prepared, the method further includes sequentially preparing a second carrier layer and a metal electrode on the surface of the wide bandgap perovskite layer.
9. A wide bandgap perovskite cell, characterized in that: It is prepared by adopting the topography control method of the wide bandgap perovskite battery as described in any one of claims 1 to 8.
10. A multi-junction stacked battery, characterized in that: It includes the wide bandgap perovskite cell as claimed in claim 9.